EFEKTIVITAS PESAN PEMBANGUNAN MELALUI BAGIAN HUMAS PEMERINTAH DAERAH BARITO KUALA DALAM MEMPERCEPAT PEMBANGUNAN DI BUMI IJE JELA (SELIDAH) KABUPATEN BARITO KUALA - Gusti Saufi Rizal (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2015)
This study aims to determine the effectiveness of Message Development through Local Government Public Relations Section Barito Kuala in Accelerating Development. The method used is quantitative and qualitative.Techniques Quantitative carried out in the preliminary study, the preliminary study was conducted with data collection using questionnaires as many as 10 people, divided into, 5 person staff part of Government Public Relations Barito Kuala, and 5 persons from the people of Marabahan, further research using Qualitative Methods by observation, interviews, documents and triangulation, carried out in four locations namely in Sub Marabahan Marabahan the District, the District Marabahan Nice Village, Village Handil Bhakti, District and Village Alalak barnacle West, District Alalak. Each study site have 5 informants as a source of information.          The study concluded socialization development policy carried out by the Local Government Barito Kuala been quite effective. Only, in the achievement of the target, socialization needs to be done to the maximum, so that the flow of information that has been channeled through various mass media is really up to the community.So, when one region disebuah area looks quite advanced, especially in terms of information and communication, not necessarily progress of the region results from the efforts being made in the region itself.